PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS X DI SMA NEGERI 1 PAITON - Anjana, Fika; Uswatun Hasanah (Madani : Journal of Social Sciences and Social Science Education, 2023)
The title of this research is "The Role of Teachers in Improving "Students' Learning Motivation in Class X Sociology Subjects at Paiton 1 Public High School". The aim of this research is to understand the role of teachers as motivators, directors and facilitators in fostering students' learning motivation in class X sociology subjects at SMA Negeri 1 Paiton. The method in this research is a qualitative method with descriptive analysis. The techniques used to obtain data in this research are observation, interviews and documentation. The subject of this research is one of the sociology teachers, namely Mr. Romdan Naufal Muttaqin and 6 class X students of SMA Negeri 1 Paiton who have low motivation Study. From the research results it can be concluded that the role of the teacher is: (1) As motivation, teachers motivate students to study hard and give warnings to students. (2) the teacher as a director has the responsibility to discipline students so they can study well in class, monitor and control students behave so that they do not break the rules in class. (3) teacher as facilitator has the responsibility to provide facilities for students, such as media in the teaching and learning process.